A Numerical Investigation of Wave‐Supported Gravity Flow During Cold Fronts Over the Atchafalaya Shelf. Issue 9 (6th September 2020) - Zang, Zhengchen; Xue, Z. George; Xu, Kehui; Ozdemir, Celalettin E.; Chen, Qin; Bentley, Samuel J.; Sahin, Cihan
Abstract: Wave‐supported fluid mud (WSFM) plays an important role in sediment downslope transport on the continental shelves. In this study, we incorporated WSFM processes in the wave boundary layer (WBL) into the Community Sediment Transport Modeling System (CSTMS) on the platform of the Coupled Ocean‐Atmosphere‐Wave‐and‐Sediment Transport modeling system (COAWST). The WSFM module was introduced between the bottommost water layer and top sediment layer, which accounted for the key sediment exchange processes (e.g., resuspension, vertical settling, diffusion, and horizontal advection) at the water‐WBL and WBL‐sediment bed boundaries. To test its robustness, we adapted the updated model (CSTMS + WBL) to the Atchafalaya shelf in the northern Gulf of Mexico and successfully reproduced the sediment dynamics in March 2008, when active WSFM processes were reported. Compared with original CSTMS results, including WSFM module weakened the overall intensity of sediment resuspension, and the CSTMS + WBL model simulated a lutocline between the WBL and overlying water due to the formation of WSFM. Downslope WSFM transport resulted in offshore deposition (>4 cm), which greatly changed the net erosion/deposition pattern on the inner shelf off the Chenier Plain. WSFM flux was comparable with suspended sediment flux (SSF) off the Atchafalaya Bay, and it peaked along the Chenier Plain coast where wave activities were strong and the bathymetric slope was steep. The influence of fluvial sediment supply on sediment dynamics was limited in the Atchafalaya Bay. Sensitivity tests of free settling, flocculation, and hindered settling effects suggested that sediments were transported further offshore due to reduced settling velocity in the WBL once fluid mud was formed. Although sediment concentration in the WBL was sensitive to surface sediment critical shear stress, cohesive bed behavior was less important in WSFM dynamics when compared with strong hydrodynamic during cold fronts. Plain Language Summary: Fluid mud is an intermediate stage between a consolidated seafloor and dilute fine sediment suspension. Its high density (>10 g/L) and downslope movement are important in sediment transport over the inner continental shelf (water depths < 15 m). In this study we adopted a numerical model to simulate fluid mud transport on the Atchafalaya continental shelf in coastal Louisiana. We found that fluid mud formed during the passages of cold fronts, and its transport contributed to offshore sediment deposition. This downslope sediment transport process was more affected by the settling velocity of sediment particles rather than fluvial supply from the Atchafalaya River or sediment consolidation on the seabed. Key Points: Model results well reproduce hydrodynamics and WSFM dynamics during cold fronts WSFM transport results in onshore erosion and offshore deposition over the Atchafalaya inner shelf Bed consolidation might influence WSFM concentration after several rounds of erosion